Quit and Win contests for smoking cessation. - Hey, K; Perera, R (2005)
BACKGROUND: Quit and Win contests were developed in the 1980s by the Minnesota Heart Health Program, and have been widely used since then as a population-based smoking cessation intervention at local, national and international level. Since 1994 an international contest has been held every two years in as many as 80 countries (2002). OBJECTIVES: To determine whether quit and win contests can deliver higher long-term quit rates than baseline community quit rates. To assess the impact of such programmes, we considered both the quit rates achieved by participants, and the population impact, which takes into account the proportion of the target population entering the contest. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group specialized register, with additional searches of MEDLINE (January 1966 to September 2004), EMBASE (180 to 2004/8), CINAHL (1982 to 2004/8) and PsycINFO (1872 to 2004/6). Search terms included competition*, quit and win, quit to win, contest*, prize*. SELECTION CRITERIA: We considered randomized controlled trials, allocating individuals or communities to experimental or control conditions. We also considered controlled studies with baseline and post-intervention measures. DATA COLLECTION AND ANALYSIS: Data were extracted by one author and checked by the second. We contacted study authors for additional data where necessary. The main outcome measure was abstinence from smoking for at least six months from the start of the intervention. We used the most rigorous definition of abstinence in each trial, and biochemically validated rates where available. We decided against performing a meta-analysis, because of the heterogeneity of the included studies, and the small number of scientifically valid studies. MAIN RESULTS: Four studies met our inclusion criteria. Three demonstrated significantly higher quit rates (8% to 20%) for the quit and win group than for the control group at the 12-month assessment. However, the population impact measure, where available, suggests that the effect of contests on community prevalence of smoking is small, with fewer than one in 500 smokers quitting because of the contest. Levels of deception, where they could be quantified, were high. Although surveys suggest that international quit and win contests may be effective, especially in developing countries, the lack of controlled studies precludes any firm conclusions from this review. AUTHORS' CONCLUSIONS: Quit and win contests at local and regional level appear to deliver quit rates above baseline community rates, although the population impact of the contests seems to be relatively low. Contests may be subject to levels of deception which could compromise the validity of the intervention. International contests may prove to be an effective mechanism, particularly in developing countries, but a lack of well-designed comparative studies precludes any firm conclusions.